2010
DOI: 10.1111/j.1541-4337.2010.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoid Metabolism in Ripening Fruits

Abstract: Ripening of fleshy fruit is a differentiation process involving biochemical and biophysical changes that lead to the accumulation of sugars and subsequent changes in tissue texture. Also affected are phenolic compounds, which confer color, flavor/aroma, and resistance to pathogen invasion and adverse environmental conditions. These phenolic compounds, which are the products of branches of the phenylpropanoid pathway, appear to be closely linked to fruit ripening processes. Three key enzymes of the phenylpropan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(139 citation statements)
references
References 166 publications
4
135
0
Order By: Relevance
“…This indicates that flavonoid response was reduced due to more production of peroxidase. The results indicated that flavonoids compete directly with other metabolites that lead to lignin biosynthesis and confirm the findings of Singh et al (2010). Since all these metabolites are required for oxidation (Boerjan et al, 2003), there would be competition in determining which resources would provide most important effects in which case there would be increased peroxidase than flavonoid as according to Moore et al (2014).…”
Section: Discussionsupporting
confidence: 73%
“…This indicates that flavonoid response was reduced due to more production of peroxidase. The results indicated that flavonoids compete directly with other metabolites that lead to lignin biosynthesis and confirm the findings of Singh et al (2010). Since all these metabolites are required for oxidation (Boerjan et al, 2003), there would be competition in determining which resources would provide most important effects in which case there would be increased peroxidase than flavonoid as according to Moore et al (2014).…”
Section: Discussionsupporting
confidence: 73%
“…For example, while volatile phenylpropanoids, such as phenylethanol, phenylacetaldehde, benzaldehyde, and benzylacetate, are generally thought to be derived from l-phenylalanine, which is formed through the shikimic acid pathway in plastids, an alternative pathway through phenyl pyruvate has recently been suggested (Orlova et al 2006). The phenylpropanoid pathway also leads to the formation of other important secondary metabolites in grapes, including hydroxycinnamates, stilbenes, lignin, lignan, aurones, flavones, isoflavonoids, as well as flavonoids, which include flavonols, tannins, and anthocyanins (Downey et al 2006, Singh et al 2010. The flavonoids are particularly important to the mouthfeel properties of red wines (Gawel 1998).…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…Interestingly, the categories for lignin, laccase and phenylpropanoid metabolism were overrepresented in ISCR regions. Genes in these processes are important in fruit flavor and ripening 31 , two of the most distinguishable differences between date palm varieties, and may thus be of value in understanding the genetic regulation of the commercially relevant properties of date palm fruit. The large number of ISCRs between the genomes analyzed here are not entirely unexpected.…”
Section: A R T I C L E S Distinguish Between the Varieties (Supplemenmentioning
confidence: 99%